Effect of growth hormone receptor gene disruption and PMA treatment on the expression of genes involved in primordial follicle activation in mice ovaries - Schneider, Augusto (Springer Netherlands, 2014)
The activation of the Pi3k-Akt1-FOXO pathway seems to be involved in the extended longevity observed in growth hormone receptor/growth hormone binding protein knockout (GHRKO) mice and is related to the growth of primordial ovarian follicles. The aim of this work was to measure the expression of genes in the ovaries of GHRKO and normal (N) mice treated with phorbol 12-myristate 13-acetate (PMA), an inhibitor of GH and IRS1 signaling. For this study, a group of N (n = 10) and GHRKO (n = 10) mice, N mice treated (n = 10) or not (n = 10) with PMA, and GHRKO mice treated (n = 10) or not (n = 10) with PMA were used. All were 6-month-old female mice. After the last PMA injection, the ovaries were collected for gene expression analysis. Expression of Amh, Gdf9, and Bmp15 was higher in GHRKO than N mice (P < 0.05), but was not different between PMA-treated N mice (P > 0.10). Expression of Amh and Gdf9 was higher (P < 0.05) for GHRKO PMA-treated mice. In addition, we observed a higher expression of Socs3 (P < 0.001) in GHRKO than N mice and a tendency for increased expression of Foxo3a (P = 0.07). For GHRKO PMA-treated mice, Foxo3a mRNA expression was higher (P = 0.02) and a tendency for higher expression of Mtor (P = 0.06) and Socs3 (P = 0.10) in GHRKO PMA-treated mice was observed. To summarize, the present data further confirm the previous histological observations that GHRKO mice have an ovarian phenotype characteristic of younger mice indicated by higher expression of Amh, Gdf9, and Bmp15 mRNA. In addition, we have shown a higher expression of Socs3 in GHRKO mice and higher Foxo3a expression in PMA-treated GHRKO mice, suggesting a role for these mediators in the process of ovarian aging.